2016
DOI: 10.1039/c6ra15764e
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable polymeric nanostructures in therapeutic applications: opportunities and challenges

Abstract: Biodegradable polymeric nanostructures (BPNs) have shown great promise in different therapeutic applications such as diagnosis, imaging, drug delivery, cosmetics, organ implants, and tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 305 publications
0
23
0
Order By: Relevance
“…Biodegradable polymeric materials show great promise in different medical applications allowing local delivery of biologically active agents and drugs. Shukla et al [154] emphasizes the state-of-the-art of biodegradable polymers and polymeric nanostructures, and discuss their future perspectives. Poly-L-lactic acid (PLLA) is the best-known biodegradable polymer, often used in manufacturing biodegradable stents (BDS).…”
Section: Polymeric Bioresorbable Stentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biodegradable polymeric materials show great promise in different medical applications allowing local delivery of biologically active agents and drugs. Shukla et al [154] emphasizes the state-of-the-art of biodegradable polymers and polymeric nanostructures, and discuss their future perspectives. Poly-L-lactic acid (PLLA) is the best-known biodegradable polymer, often used in manufacturing biodegradable stents (BDS).…”
Section: Polymeric Bioresorbable Stentsmentioning
confidence: 99%
“…Intensive research on the improvement of functional characteristics and biocompatibility of PLLA as well as poly(lactide-co-glycolide) (PLGA) has been conducted over the last years. Other PLLA-based stents, for example Elixir (Sunnyvale, CA, USA), ARTDIVA from Arterial Remodeling Technologies (Noisy le Roi, France), Tissue Gen (Dallas, TX, USA), and others [23,154], are also under investigation. The extensive discussion of the related results can be found in several reviews [21,22].…”
Section: Polymeric Bioresorbable Stentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymeric nanomaterial‐based drug delivery systems, due to their flexibility and biodegradability, have shown great potential in biomedical applications including drug delivery, diagnosis, therapeutic, and tissue engineering . Many studies have demonstrated that polymeric nanomaterials like polymeric micelles, nanocapsules, nanogels, dendrimers, and polymeric hybrid NPs could be used as nanocarriers to deliver water‐insoluble anticancer drugs, peptides, proteins, DNA, and RNA to the desired site of action (Figure b). Similar to liposomes, polymeric nanomaterials also improve the solubility and stability of the encapsulated drugs, as well as their therapeutic effects due to a greater fraction of drug reaching the target site .…”
Section: Recent Discoveries In Nanotoxicology and Nanomedical Implicamentioning
confidence: 99%
“…[15][16][17][18] With advantages in increasing circulation times, controlling drug release, reducing drug toxicity, improving bioavailability and targeting speci¯c sites, nanoparticles (NPs), such as calcium phosphates and carbon nanotubes, have been used to overcome the limitations of conventional chemotherapeutic treatments. [19][20][21][22] Though there have been several studies about CuS NPs as drug delivery systems, papers mentioned GFLG connecting to CuS NPs are few.…”
Section: Introductionmentioning
confidence: 99%